Produção de RPG como metodologia ativa no ensino de literatura e língua portuguesa - Morais, Robson de Sousa (2024)
The contemporary educational context comprises technological elements that spread beyond the school and pose challenges for the training and exercise of teaching in the various curriculum components that make up the National Common Curricular Base (BNCC). Considering the teaching of Portuguese Language and Literature in the context of public education, the severe reading difficulties highlighted by the last edition of the PIRLS (Progress in International Reading Literacy Study) study still stand out at the time of writing this work. The demand for innovative educational practices and paradigms, guided by modern and stimulating technologies, capable of redefining the role of teachers and expanding their ability to interact with students who are native users of these technologies, is evident. Games within an educational spectrum have proven to be an attractive way to capture students’ interest and encourage their participation. Thus, this work investigates the use of games, more specifically through the creation and construction of Solo Role-Playing Games (RPGs), as a potentiating element for the teaching and learning Literature, from a constructionist and contextualized perspective. It is hypothesized that the codesign of games provides students greater participation and protagonism in the teaching-learning process and broader and more diversified training for teachers working at the basic education level. The educational product of this proposal is a didactic sequence that will guide the teacher in replicating the methodology in the classroom in light of the BNCC for the development of analog games according to the planned program content. The audience and the locus of this research were students and schools of High School integrated into the Public Education Network of Ceará. The evaluation was elaborated in two stages, the first based on a questionnaire applied before the production of the games, followed by the analysis of the understanding of the contents and skills explored in the methodology proposed in this research through assessments.